Exploring the dynamics of power: a Foucauldian analysis of care planning in learning disabilities services - Gilbert, Tony (Nursing inquiry, 2003)
Exploring the dynamics of power: A Foucauldian analysis of care planning in learning disabilities services This paper draws upon a study completed in 2000 that focused upon health and welfare provision for people with learning disabilities in one English county. This study drew upon the theoretical insights of Michel Foucault to provide an analysis of the micro politics of care planning. This involved the analysis of text from two sources: the academic literature and interview material gained from a number of professionals working in health and welfare services for people with learning disabilities. Drawing upon this research material, the first part of this paper briefly explores the relationship between policy, professional practice and the people who are the subjects of that practice. The discussion then moves on to consider Foucault's five methodological precautions and the way power produces a localised web of activity that identifies specific targets for management. In this process power draws into the web a range of informal and formal practices that initially lie outside of the web. The discourse produced through the activity surrounding care planning provides the evidence of this flow of power. This discourse then takes on the status of science (truth), which reproduces this activity.